Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1088/1755-1315/1080/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity of Iraqi western desert and surroundings: As an example of continental intraplate seismicity

Abstract: Seismicity of Iraqi western desert and surroundings was investigated using a complete and unified magnitude earthquake catalog covering the interval from 1900 to 2017. A marked rise in number of the events in the study area was observed after the year 2000 compared to the previous years. The magnitude of majority of the recorded events ranged from 2 to 3.5 Mw. The value of b-constant in frequency-magnitude relation is 0.7. The epicentral distribution shows that the western desert is aseismic to very low seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The Badra-Amarah fault, which runs along the Iraqi-Iranian border and is thought to be the most seismically active fault in Iraq, the Euphrates fault, the Hummar fault (north of Basra), the Al-Refaee fault, and the Kut fault are all seismically active faults in the Mesopotamian Foredeep [37]. A recent study of the seismicity of the Western Desert and its surrounding areas, which represent an important part of the Inner (stable) Arabian Platform, showed that the region was exposed to earthquakes ranging in size from 2 to 3.5, during the period from 1900 to 2017 [55]. The epicenters were grouped into five seismic zones.…”
Section: Seismicity Of Iraqmentioning
confidence: 99%
“…The Badra-Amarah fault, which runs along the Iraqi-Iranian border and is thought to be the most seismically active fault in Iraq, the Euphrates fault, the Hummar fault (north of Basra), the Al-Refaee fault, and the Kut fault are all seismically active faults in the Mesopotamian Foredeep [37]. A recent study of the seismicity of the Western Desert and its surrounding areas, which represent an important part of the Inner (stable) Arabian Platform, showed that the region was exposed to earthquakes ranging in size from 2 to 3.5, during the period from 1900 to 2017 [55]. The epicenters were grouped into five seismic zones.…”
Section: Seismicity Of Iraqmentioning
confidence: 99%